The Environmental, Social and Economic Sustainability of Agriculture in the Dry Areas - Solh, Mahmoud; Fattal, Lamia EL (Annals of Arid Zone, 2016)
This overview addresses the current challenges faced by farmers and pastoralists in the drylands of developing countries who depend on agriculture and livestock for their livelihoods. Many farmers and pastoralists in the drylands are trapped in a perpetual cycle of poverty, poor crop yields, scarcity of natural resources - particularly water, and a lack of supportive policies and institutions. The rapidly increasing population and a markedly higher vulnerability to climate change in other parts of the world will continue to aggravate the challenges faced by local communities. Existing science and technology tools and resources offer the capability to increase sustainable agricultural intensification in the drylands. The impacts resulting from ICARDAâ€™s research in partnership with national research and extension systems clearly demonstrate the vital role of science and technology in improving the livelihoods of dryland populations. Further, the need exists to adopt an integrated or â€œsystemsâ€ approach to bring together all stakeholders and develop technologies, resource management strategies, and institutional arrangements that are capable of solving the daunting problems confronting dry area production systems. Key words: Dry lands, developing countries, partnerships, systems approach, environmental sustainability, social sustainability, economic sustainability, ICARDA, food security, water.